TI_GERICHTE 90.2005.10 vom 23. Mai 2006 , non attribuzione alla zona edificabile di un fondo assegnato alla zona agricola - TI Tribunale d'appello (2006)
non attribuzione alla zona edificabile di un fondo assegnato alla zona agricola